Selection and Outcomes in Abdominoperineal Resection - Garcia-Henriquez, Norbert; Galante, Daniel J.; Monson, John R. T. (Frontiers in Oncology, 2020)
Since the initial descriptions of the abdominoperineal resection by Sir William Ernest Miles which was then followed by the perfection of the total mesorectal excision by Professor Bill Heald, the surgical management of rectal cancer has made tremendous strides. However, even with the advent and sophistication of neoadjuvant therapy, there remains a formidable amount of patients requiring an abdominoperineal resection. The purpose of this review is to delineate the indication and selection process by which patients are determined to require an abdominoperineal resection, as well as the oncologic and overall outcomes associated with the operation.